Losing the Monopoly of Violence: The State, a Drug War and the Paramilitarization of Organized Crime in Mexico (2007––10). (1st April 2015) - Guadalupe Correa-Cabrera; Michelle Keck; José Nava
Abstract : This article examines the phenomenon of drug-related violence in Mexico and the causal factors that enabled the upsurge in the numbers of drug-related homicides during the period 2007––10 —— the first 4 years of the so-called ""war on drugs"". The authors explore regional statistics derived from official sources, as well as from both anecdotal and empirical research on the subject, and assess quantitatively the impact of different factors such as deteriorated economic conditions, corruption, a new configuration of organized crime, divisions between criminal organizations and the Mexican government's strategy to fight organized crime. The study finds that the key forces that explain a massive increase in violence in the most recent years are the involvement of the federal forces in the fight against drug trafficking organizations (the State), the splits between criminal syndicates and what is defined here as the ""paramilitarization"" of organized crime in Mexico. Finally, the present analysis makes use of Max Weber's (1919) ""monopoly of violence"" framework, and explains how the Mexican State has been losing this monopoly in recent years.